Intimate Friendship: The Foundation of Students' Self-Efficacy at SMP Negeri 8 Palangka Raya - Sarifah, Siti; Surawan, Surawan (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to find out how to build self-efficacy through intimate friendship. The research subjects were class VII students at SMP Negeri 8 Palangka Raya. This type of research is descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The data analysis technique uses qualitative data analysis using the Miles and Huberman model. The results of the research show that efforts to build self-efficacy through intimate friendship can be done by: a student must have a sense of sensitivity to other people's emotional situations so that in a group they can share and encourage each other so that they can build one's self-efficacy to solve the problems faced, a students must show an open attitude and be able to take experience from someone who has previously succeeded in close friendships so that the perception will emerge that he can also complete the task at hand, a student can show an attitude of loyalty and sacrifice in friendship, so that when one of his friends has difficulty learning can form mutual cooperation to solve assignment problems, a student can show an honest attitude so that friendships avoid toxic friendships so that friendship relationships based on positive emotions will build increasing self-efficacy.